1998
DOI: 10.1093/ajcn/68.3.623
|View full text |Cite
|
Sign up to set email alerts
|

Serum retinol concentrations in children are affected by food sources of ²-carotene, fat intake, and anthelmintic drug treatment

Abstract: The provision of vitamin A in food sources of beta-carotene is an alternative to the distribution of high-dose capsules. To examine factors that may influence the success of food-based programs, a study was carried out in Sumatra, Indonesia, of the effect of food sources of beta-carotene, extra dietary fat, and Ascaris lumbricoides infection on serum retinol concentrations in children. Meals and snacks with various amounts of beta-carotene and fat were fed at midday to children 3-6 y of age for 3 wk. Some grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(137 citation statements)
references
References 17 publications
4
131
0
2
Order By: Relevance
“…Jalal et al (1998) in their 3 week intervention study included children aged 3 ± 6 y positive for Ascaris lumbricoides with a baseline serum retinol concentration of 0.57 ± 0.66 mmolal. They found that b-carotene-rich foods (750 REaday mainly in the form of red sweet potatoes for a total cumulative dose of 15 750 RE) together with deworming increased serum retinol more than b-carotene rich foods alone in children heavily infected with Ascaris lumbricoides ( b 3200 epg) (net increase 0.37 compared to 0.20 mmolal).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jalal et al (1998) in their 3 week intervention study included children aged 3 ± 6 y positive for Ascaris lumbricoides with a baseline serum retinol concentration of 0.57 ± 0.66 mmolal. They found that b-carotene-rich foods (750 REaday mainly in the form of red sweet potatoes for a total cumulative dose of 15 750 RE) together with deworming increased serum retinol more than b-carotene rich foods alone in children heavily infected with Ascaris lumbricoides ( b 3200 epg) (net increase 0.37 compared to 0.20 mmolal).…”
Section: Discussionmentioning
confidence: 99%
“…However, in one of the studies with poor DGLV response (de Pee et al, 1998), the mean baseline retinol concentration was`0.70 mmolal, de®ning it as a group with a severe VAD problem (WHOaUNICEF, 1995). Another cause for poor response could be intestinal parasites, in particular Ascaris lumbricoides (Curtale et al, 1994;Jalal et al, 1998). It has been postulated that`a high parasite load may make the freeing of b-carotene more dif®cult from a complex matrix (vegetables) ' (de Pee et al, 1995a).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have failed to detect any effects (Ahmed et al, 1993). Associations between A. lumbricoides infection and low serum retinol have been found among preschool children in Panama (Taren et al, 1987) and Nepal (Curtale et al, 1994), as well as among Indonesian preschool children where the low serum retinol was reversible after deworming (Jalal et al, 1998). In contrast, another study among young children in Indonesia found neither effect of deworming on serum retinol nor modified relative dose response test (Tanumihardjo et al, 1996).…”
Section: S Mansoni and Geohelminth Infectionsmentioning
confidence: 99%
“…Another way of reducing matrix effects is by homogenization or particle size reduction (van Zeben & Hendriks, 1948;Gärtner et al, 1997;Castenmiller et al, 1999;van het Hof et al, 1999). Dietary fat, as well, has a documented positive effect on bioavailability of carotenoids (Roels et al, 1958;Dimitrov et al, 1988;Shiau et al, 1994;Jalal et al, 1998), although the amount of fat required to optimize carotenoid bioavailability has not been clearly identified.…”
Section: Introductionmentioning
confidence: 99%